“CEO“ Applications in Modern Sports Management. - Atalay, A, Yücel, A. S. (My University, 2013)
Olympic Games, World Cups, Continental Championships, sometimes even local Sportive Organizations of nations arouse a global interest across the world. This interest becomes widespread by means of media as a progress indicator of information technologies. As the number of sports viewers reach to billions, this situation enables rapid increase of earning rates obtained from live transmission, sponsorship, advertisement and sales of licensed goods. Present situation makes the adoption of a commercial and professional viewpoint necessary for the clubs to continue their existence and to strengthen financially. Chief Executive Officers (CEO’s) who develop, execute prospective strategic policies of the company he/she is working for and inspect the things done, and who have characteristics of a theoretician and practitioner, appear as a powerful director type candidate to fill the void in the club administrations. In this study, we tried to establish applicability of CEO’s, with whom we confront in the general business management, within the organizational and commercial administrative mentalities of sports clubs that have part in the sports sector and turned into a business organizations.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Sports; Sports Management; CEO Applications in Sports Management